Territorial narratives: an analysis of wine labels of the Old and the New World - Henrique de Siqueira Leite, Pedro; de Moraes Andrade Barbosa, Ana Carolina (InfoDesign, 2024)
This article aims to investigate the existing territorial narratives on wine labels. Therefore, the contributions of design on packaging were observed, more specifically on forty wine labels, in a comparison of strategies from the two production poles: twenty from the Old World and twenty from the New World. For the analytical method, the focus was the correlation of technical information and elements of visual communication, analyzing the hierarchical and differentiating variables of the informational system and the application of visual language attributes in the selected sample. That way, it was possible to perceive that, depending on the place, different information is emphasized, creating new dynamics of meaning so that not only technical information is presented, but also an experience that brings the producer closer to the buyer closer through characteristics that resemble traditions of the vitivinicultural universe.